John Marquand House, detail of corner columns, Cambridge, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
Detail view of the John Marquand House in Cambridge, Massachusetts. Example of the Queen Anne style, with a two story porch.; Caption on image: John Marquand house Camb. Queen Anne 2 story porch.; Binder Number 4. Pocket Number: 14.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.